MENIMBANG BADAN PERADILAN KHUSUS PASKA PUTUSAN MK - Nasarudin Sili Luli (Journal of Social Sustainability Management, 2022)
The Constitutional Court (MK) annulled the existence of a special judicial body regulated in Article 157 paragraphs (1) and (2) of Law No.10/2016 concerning the Stipulation of Government Regulations in Lieu of Law Number 1 of 2014 concerning the Election of Governors, Regents, And Mayor. The Constitutional Court emphasized that because there is no longer any difference between national general elections and regional head elections, the Constitutional Court is the only institution authorized to adjudicate at the first and final levels whose decisions are final for, among other things, deciding disputes over the results of general elections. In its decision, the MK granted the petition for review of Article 157 paragraphs (1) and (2) of the Election Law against the 1945 Constitution that was requested by the Association for Elections and Democracy (Perludem). “To grant the petition of the Petitioner in its entirety.